Pelaksanaan Pendampingan Aktivitas Studi Independen Kampus Merdeka di Yayasan Sekolah Ekspor Nasional - Alunaza, Hardi; Mentari, Mentari (Journal of Community Development, 2024)
In today's era of globalization, where the boundaries between countries are increasingly blurred and international trade is on the rise, it is important for students to understand the export-import skills. With a strong understanding of international trade, students can expand their career opportunities, broaden their insights into global markets, help address social and environmental challenges related to international trade, expand their professional networks, and become responsible global citizens. A policy that can accommodate students' needs regarding the above issues is the Kampus Merdeka policy. The mentoring activities for the studi independen process of Kampus Merdeka are based on the needs of students regarding the importance of having supervising lecturers who can serve as consultation points to ensure the success and effectiveness of the program. This mentoring activity is carried out during the period from February to April 2024. The objective of implementing this mentoring process is to ensure that a total of 50 students under the guidance of lecturers can successfully complete the program at Yayasan Sekolah Ekspor Nasional. The mentoring activities are conducted using three methods: mentoring, consultation and evaluation, as well as documentation and reporting. The results of this mentoring process indicate that out of the 8 competencies offered by the partners, students obtained the highest average scores in the export payment and documentation competency with a score of 91.2 and Continuous Improvement with a score of 96.8. Meanwhile, the two competencies with the lowest average scores are Export Logistics with a score of 65 and Export Research and Strategy with a score of 65.6. The recommendations include the creation of a learning calendar by the Kampus Merdeka team and partners, should also be communicated to the program's mentor and lecturer, and the coordination between  mentor and the lecturer needs to be improved.